Rural European population facing the challenges of global citizenship education - Marbán, José María; Santamaría-Cárdaba, Noelia; Torrego-Egido, Luis (Iberoamerican Journal of Development Studies, 2022)
Supporting the creation of a critical citizen, with deeply rooted community values of solidarity and active compromise to the spread and development of those values, is making means believing in a better world in which no one can nor should feel excluded. Nevertheless, this is met with differing opinions. This study approaches attitudes towards Global Citizenship Education specifically though the framework of the population of rural Europeans who participated in the Rural DEAR Agenda ‒ EYD 2015 Project. In order to do, quantitative research was carried out based on a survey and questionnaire developed. The questionnaire focused on interest in international solidarity; for example, opinions and attitudes towards injustices suffered by impoverished countries, as well as opinions surrounding the possibility of changing this situation. The results obtained reveal a shocking reality in many ways relative to international solidarity and a low level of compromise regarding taking action to change the current situation.